Pengaruh Pemberian Pakan Buatan Berbeda Kandungan Protein terhadap Pertumbuhan Berat Ikan Molly (Poecilia sphenops) Ukuran 4cm di Bak Pemeliharaan - Anjaina Elina Salma; Maria Agustini; Indra Wirawan (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Molly fish (Poelicia sphenops) is a freshwater ornamental fish commodity which is a type of "livebearer" fish or stores eggs in the body and gives birth to larvae. The research method used in this research is an experimental method. The aim of this research is to determine the effect of giving artificial feed with different protein content on the weight growth of molly fish and determine the appropriate dose of artificial feed for weight growth of molly fish. It is hoped that the benefits of this research will increase scientific insight in the fisheries sector, especially in the use and influence of artificial feed with different protein content on molly fish weight growth to advance the fisheries sector. The content in feed pf 0-100 protein is 39 - 41%, takari feed is 30% protein, mem feed is 60% protein. Each treatment in this study was carried out in 8 repetitions.